New teaching concept for chinese language - Daulet F.N., F N (Journal of Oriental Studies, 2016)
In the given article, the author presented the new concept of teaching Chinese language. The article is based on competence-oriented and person-oriented educational technology presented in the textbook «Practical Course of Chinese. The new concept of teaching».Based on the lessons learned from the textbook, the author paid attention to the use of pedagogical theories.